Sleep Disturbances in Young Adults with Childhood Traumatic Brain Injury: Relationship with Fatigue, Depression, and Quality of Life. (14th October 2020) - Botchway, Edith N.; Godfrey, Celia; Ryan, Nicholas P.; Hearps, Stephen; Nicholas, Christian L.; Anderson, Vicki A.; Catroppa, Cathy
ABSTRACT: Objective: This study assessed the consequences of childhood traumatic brain injury (TBI) on sleep, fatigue, depression, and quality of life (QoL) outcomes and explored the relationships between these variables at 20 years following childhood TBI. Participants: We followed up 54 young adults with mild, moderate, and severe TBI, and 13 typically developing control (TDC) participants, recruited at the time of TBI. Methods: Sleep was assessed with the Pittsburgh Sleep Quality Index and actigraphy. Results: At 20 years postinjury, results showed no significant difference between whole TBI group and TDC participants on subjective sleep quality; however, the moderate TBI group reported significantly poorer subjective sleep quality compared to those with severe TBI. Poorer subjective sleep was associated with increased symptoms of fatigue, depression, and poorer perceptions of General Health in the TBI group. Actigraphic sleep efficiency, fatigue, depression, and QoL outcomes were not significantly different between TBI and TDC or among TBI severity groups. Conclusions: These preliminary findings underscore associations between subjective sleep disturbance, fatigue, depression, and QoL in this TBI sample, and mostly comparable outcomes in sleep, fatigue, depression, and QoL between the TBI and TDC groups. Further research is required to clarify these findings.